His bundle pacing in heart failure: A review of current literature - Chaudhary, Rahul; Garg, Jalaj (Journal of Cardiology and Cardiovascular Medicine, 2020)
Biventricular (BiV) pacing revolutionized the heart failure management in patients with sinus rhythm and left bundle branch block; however, left ventricular-lead placement is not always technically possible. Also, BiV pacing does not fully normalize ventricular activation and, therefore, the ventricular resynchronization is imperfect. On the other hand, right ventricular pacing for bradycardia may cause or worsen heart failure in some patients by causing dyssynchronous ventricular activation. His bundle pacing comes as an alternative to current approaches as it activates the ventricles via the native His-Purkinje system, resulting in true physiological pacing, and, therefore, is a promising site for pacing in bradycardia and traditional CRT indications in cases where it can overcome left bundle branch block. Furthermore, it has the potential to open up new indications for pacing therapy in heart failure, such as targeting patients with PR prolongation, but a narrow QRS duration. In this article we explore the history, clinical evidence, proposed mechanisms, procedural characteristics, and the role in current therapy of His bundle pacing in the prevention and treatment of heart failure.